A Nonaqueous Na‐Ion Hybrid Micro‐Supercapacitor with Wide Potential Window and Ultrahigh Areal Energy Density. Issue 11 (12th August 2019) - Zhang, Panpan; Wang, Lanlan; Wang, Faxing; Tan, Deming; Wang, Gang; Yang, Sheng; Yu, Minghao; Zhang, Jian; Feng, Xinliang
Abstract: The increasing demand on smart miniaturized electronics has greatly boosted the development of high‐performance micro‐supercapacitors (MSCs). However, the unsatisfied electrochemical performance (e. g., narrow potential window, low areal energy density) impedes their wide applications. Here, we demonstrate a novel type of nonaqueous Na‐ion hybrid MSC, using VS2 nanosheets grown on electrochemically exfoliated graphene (VS2 @EG) as the negative electrode and activated carbon as the positive electrode in nonaqueous sodium‐ion electrolyte. Such constructed nonaqueous Na‐ion hybrid MSCs show a remarkable areal capacitance of 110.7 mF cm −2 at 0.2 mA cm −2 in a wide potential range of 0.01–3.5 V and an outstanding areal energy density of 188.3 μWh cm −2 . Besides, an impressive cycling stability up to 5000 cycles without noticeable decay is also achieved for the nonaqueous Na‐ion hybrid MSCs. This new hybrid MSC holds great potential application in on‐chip electronics. Abstract : A wider window for the win : A nonaqueous Na‐ion hybrid micro‐supercapacitor with high operating voltage window and ultrahigh areal energy density is successfully constructed by using pseudocapacitive VS2 @EG anode and capacitor‐type activated carbon cathode in a NaClO4 ‐contained organic electrolyte. This work provides a new strategy for developing novel pseudocapacitive materials and next‐generation miniaturized energy storage devices.